ORAL MANIFESTATIONS IN CHILDREN WITH DOWN SYNDROME - Dewi Nurnaini, Lasmi; Widyanoya, Arwinda (Fakultas Kedokteran Gigi Unjani, 2025)
Down syndrome is an autosomal genetic disorder that can occur in both men and women, with an extra chromosome 21. This literature review aimed to determine the oral manifestations and management of patients with Down syndrome. The method used in this literature review involved reviewing relevant national and international journal articles related to Down syndrome and its oral manifestations, retrieved from databases such as PubMed, ScienceDirect, and Google Scholar. The results of this literature review showed that children with Down syndrome have several clinical features, such as muscle hypotonia, brachycephaly, flat nose, hypersalivation, and various comorbid systemic diseases, such as congenital heart defects. Oral manifestations included mouth breathing, open bite, macroglossia, delayed tooth eruption, dental agenesis, caries, periodontal disease, and dental anomalies. Behavior management in patients with Down syndrome is something that must be considered so that tooth treatment can be carried out optimally. DOI : 10.54052/jhds.v5n1.p19-30